2003
DOI: 10.1538/expanim.52.11
|View full text |Cite
|
Sign up to set email alerts
|

Preference of Guinea Pigs for Bedding Materials: Wood Shavings versus Paper Cutting Sheet.

Abstract: Abstract:The preference of guinea pigs for bedding materials, wood shavings (WS) or paper cutting sheets (PS), was studied. Animals aged 8 weeks and 20 weeks showed a similar behaviour pattern during 30 min in the light, preferring WS to PS regardless of ages. Over both light and dark periods for 24 h, guinea pigs apparently preferred WS in the light, spending much more time resting in them than in PS. In the dark, the border-crossing was significantly more frequent than in the light, and the staying time was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The mice stayed on Shepherd-shack TM longer in the dark, which is a more active time for mice. The mouse is a nocturnal animal, and eating, drinking and excretion behaviour are mostly conducted in darkness [9,17]. By staying in both cages, Agrebe TM and Shepherd-shack TM , the mice suggested the differences in kinds of behavior between in the light and dark periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mice stayed on Shepherd-shack TM longer in the dark, which is a more active time for mice. The mouse is a nocturnal animal, and eating, drinking and excretion behaviour are mostly conducted in darkness [9,17]. By staying in both cages, Agrebe TM and Shepherd-shack TM , the mice suggested the differences in kinds of behavior between in the light and dark periods.…”
Section: Discussionmentioning
confidence: 99%
“…To date, wood chips, paper and others have been [2,4,9,16]. However, the increasing interest in protecting the environment and natural resources requires alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Guinea pigs given the option of wood shavings versus paper sheets for bedding spent significantly more time during the light cycle in areas of the cage bedded with wood shavings than with paper sheets, yet had a slight preference for paper sheets under dark conditions (Kawakami et al, 2003.) Wire-mesh flooring may result in injuries to feet and legs and reduced production in breeding animals, and should be avoided unless deemed necessary for experimental purposes.…”
Section: Laboratory Management and Husbandrymentioning
confidence: 99%
“…Guinea pigs move, rest, and often eat as groups, with activity occurring both day and night , although some authors state that guinea pigs are usually nocturnal (Kawakami et al, 2003). In a cage without adequate sheltering sites, guinea pigs align along the cage perimeter, end to end, with pups near the end of the line.…”
Section: Behaviormentioning
confidence: 99%
“…Thus, each call can have multiple meanings or uses based on context. One study found that bedding preference, for wood shavings versus shredded paper, varied depending on time of day (Kawakami et al, 2003). White et al (1990) suggested that guinea pigs did not utilize the whole of the cage area; however, Scharmann (1991) found that when the cage was enriched through the addition of hay and straw, then they burrowed and hid in it.…”
Section: E Guinea Pigsmentioning
confidence: 99%